High-accuracy teslameter with thin high-resolution three-axis Hall probe. (February 2017) - Popovic Renella, Dragana; Dimitrijevic, Sasa; Spasic, Sasa; Popovic, Radivoje S.
Highlights: The digital teslameter incorporates a 3-axis Hall probe that is only 250 μm thick. Single silicon chip with integrated horizontal and vertical Hall devices. Measuring magnetic field vectors with the spatial resolution of 100 μm. Magnetic resolution of ±2 ppm of the range; accuracy of 0.001% of the range. Temperature coefficient is less than 5 ppm/°C; and angular errors are less than 0.1°. Abstract: The new digital teslameter system (also called Gaussmeter) incorporates a 3-axis Hall probe, analog electronics based on the spinning-current technique, 24-bit analog-to-digital converter, computer, and 7-digit touch-screen display. The Hall probe is a single silicon chip with monolithically integrated horizontal and vertical Hall magnetic sensors and a temperature sensor. The Hall sensor chip is encapsulated in a robust ceramic package, a version of which is only 250 μm thick. The spinning-current eliminates most of the Hall probe offset, low-frequency noise, and the planar Hall voltage. The errors due to the Hall element non-linearity and the variations in the probe electronics temperatures are eliminated by a calibration procedure based on a three-variable second-order polynomial. The errors due to the angular errors of the Hall probe are eliminated by a calibration of the sensitivity tensor of the probe. These new developments resulted in a teslameter that can measure magnetic field vectors from about 1 μT to 30 T, with the spatial resolution 100 μm, magnetic resolution ±2 ppm of the range, the accuracy ±0.0001% of reading +0.001% of range, temperature coefficient less than 5 ppm/°C, and angular errors less than 0.1 deg.